Challenges faced by students in completing a MOOC - Ismail, Zuraidah; Kamalludeen, Rosemaliza (PEN Academic Publishing, 2020)
This study was conducted to explore the challenges faced by students in completing a MOOC (Massive Open Online Course). Participants selected for this study were restricted to post graduate students only who came from Iraq, Malaysia, Somalia and Oman. The number of students selected for this research was 6 with two master’s students and four PhD students. MOOC is having problem of low completion rates and this is a big issue all over the world now. Despite the growing interest in MOOCs, the vast majority of students who have enrolled in MOOCs do not finish the courses. Hence, the purpose of the study is aimed at looking at the challenges faced by students in completing MOOCs. Qualitative mode was used for this study and all the students were interviewed for data gathering. The results indicated that the problems students faced in completing MOOCs are in terms of MOOC content, MOOC activity, MOOC design, MOOC instructors, accessibility and cost.